2019
DOI: 10.3390/nu11102271
|View full text |Cite
|
Sign up to set email alerts
|

Catechin and Procyanidin B2 Modulate the Expression of Tight Junction Proteins but Do Not Protect from Inflammation-Induced Changes in Permeability in Human Intestinal Cell Monolayers

Abstract: The possibility of counteracting inflammation-related barrier defects with dietary compounds such as (poly)phenols has raised much interest, but information is still scarce. We have investigated here if (+)-catechin (CAT) and procyanidin B2 (PB2), two main dietary polyphenols, protect the barrier function of intestinal cells undergoing inflammatory stress. The cell model adopted consisted of co-cultured Caco-2 and HT29-MTX cells, while inflammatory conditions were mimicked through the incubation of epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 63 publications
1
35
0
Order By: Relevance
“…Studies on intestinal dysfunction have employed human colon carcinoma cell lines, with Caco-2 being the most well-established and widely used model of the human intestine barrier ( [105] and Table 1). Mucus producer [106], macrophages [107], and B cell lines [108] have been employed in co-culture systems to explore the interaction between cell populations. Although there is a strong trend in the industry towards replacing animal experiments with human cell-culture based models [109,110], there are no in vitro models of the human intestine that replicate the complex interplay between cell types and the regulation of the barrier function by the mucosal innate and adaptive immunity.…”
Section: Studies On the Benefits Of Pacs For Intestinal Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on intestinal dysfunction have employed human colon carcinoma cell lines, with Caco-2 being the most well-established and widely used model of the human intestine barrier ( [105] and Table 1). Mucus producer [106], macrophages [107], and B cell lines [108] have been employed in co-culture systems to explore the interaction between cell populations. Although there is a strong trend in the industry towards replacing animal experiments with human cell-culture based models [109,110], there are no in vitro models of the human intestine that replicate the complex interplay between cell types and the regulation of the barrier function by the mucosal innate and adaptive immunity.…”
Section: Studies On the Benefits Of Pacs For Intestinal Dysfunctionmentioning
confidence: 99%
“…Some in vitro studies have associated PACs with increased TEER and decreased transport of permeability markers in the context of barrier dysfunction [115][116][117]. The expression levels of TJ proteins (claudins, occludins, and ZOs) often correlate, but not always [106], with intestinal permeability and are also considered markers of epithelial integrity. Bitzer et al [116] found that the dextran sodium sulphate (DSS)-induced loss of barrier function in Caco-2 cells was significantly inhibited by polymeric PACs of cocoa but not by oligomers.…”
Section: Nd [106]mentioning
confidence: 99%
See 1 more Smart Citation
“…This is of interest to further studying the bioactivity of the compounds in the extracts. Bianchi et al [ 17 ] looked at the role of key dietary flavan-3-ols, (+)-catechin and procyanidin B 2 , in protecting the barrier function of intestinal cells undergoing inflammatory stress. The authors highlighted how, under the physiological conditions adopted, these compounds did not prevent inflammation-dependent impairment of the epithelial barrier function.…”
mentioning
confidence: 99%
“…The authors highlighted how, under the physiological conditions adopted, these compounds did not prevent inflammation-dependent impairment of the epithelial barrier function. Nevertheless, these flavan-3-ols modified the expression of tight-junctional proteins and, in particular, claudin-7, shedding light on the potential biological activity of these major dietary flavan-3-ols at the intestinal level [ 17 ]. Our research group, in collaboration with other teams, also assessed the capability of the main colonic metabolites of flavan-3-ols, phenyl-γ-valerolactones, to reach the brain by crossing the blood-brain barrier [ 18 ].…”
mentioning
confidence: 99%